Comparison of Tropospheric Signal Delay Models for GNSS Error Simulation - Hye-In Kim; Jihyun Ha; Kwan-Dong Park; Sanguk Lee; Jaehoon Kim (Journal of Astronomy and Space Sciences, 2009)
As one of the GNSS error simulation case studies, we computed tropospheric signal delays based on three well-known models (Hopfield, Modified Hopfield and Saastamoinen) and a simple model. In the computation, default meteorological values were used. The result was compared with the GIPSY result, which we assumed as truth. The RMS of a simple model with Marini mapping function was the largest, 31.0 cm. For the other models, the average RMS is 5.2 cm. In addition, to quantify the influence of the accuracy of meteorological information on the signal delay, we did sensitivity analysis of pressure and temperature. As a result, all models used this study were not very sensitive to pressure variations. Also all models, except for the modified Hopfield model, were not sensitive to temperature variations.